DESAIN PENDIDIKAN PRA NIKAH MENUJU TERBENTUKNYA KELUARGA SAKINAH - Wardian Wardian (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
In the current global situation where media and information access is very heavy and unstoppable, it will directly or indirectly affect the behavior of adolescents either in the form of positive or negative behavior. Teachers with specific physical and psychological characteristics are age groups that tend to be vulnerable to have various problems which must be faced with a special approach. Biological maturity in adolescence in the sense of maturity of reproductive organs followed by interest with the opposite sex often not accompanied by psychological maturity.Maka, when fostering households not infrequently ended in divorce. Moreover, the phenomenon of divorce is happening today many proposed by the wife through sued for divorce against her husband. Therefore, it is important to hold premarital education for married young people to minimize the occurrence of divorce and expected to help realize the formation of household (sakinah, mawaddah and rahmah). Starting from the above issues, then the issues raised in this paper are what factors are the cause of the divorce and the descriptions of pre-marriage education that how so that it can help for couples who want to marry towards the formation of sakinah family? The purpose of writing this scientific paper is to know what factors are the cause of divorce in society and to know the design of pre-marriage education that can help for couples who want to marry toward the formation of sakinah family. Through this paper is expected to contribute constructive and useful thoughts for the community, especially for young people married about what things should be done before marriage so that later when fostering households can help realize the family sakinah, mawaddah, and rahmah. By using the theory of maturity of married age and the purpose of marriage and qualitative descriptive approach through literature review, it can be concluded that the factors causing divorce in the household are due to economic factors, infidelity, abuse and domestic violence (KDRT), unhealthy polygamy , domestic disharmony, jealousy, forced marriage, underage marriage, and biological disability (unable to meet biological needs), political differences, and family interference. As for the realization of a sakina family it is necessary to design a pre-marriage education systematically and well planned through: a) pre-marital education in the family environment, b) pre-marital education at school, c) the curriculum of pre-marital education on campus, d) future bride and groom. Keywords: Teenagers, Maturity or Full-grown, Married Age, Divorced, Pre-Marriage Education, Sakinah Family.